أثر إستخدام التسويق الفيروسي على ولاء المستهلك الجزائري للعلامة التجارية سامسونج "samsung " -دراسة ميدانية تحليلية- - سليمة, مخلوف (Université de M'sila, 2020)
ملخص: يهدف هذا البحث إلى دراسة ولاء المستهلك الجزائري للعلامة التجارية سامسونج "Samsung " بإستخدام التسويق الفيروسي. ولتحقيق هدف الدراسة قامت الباحثة بجمع المعلومات اللازمة عن طريق استبانة تمّ تطويرها لهذا الغرض بعد إخضاعها لاختباري الثبات صدق. أجريت الدراسة على عينة ميسرة تمّ إختيارها من مجتمع الدراسة، و هم المستهلك الجزائري من مستخدمي العلامة التجارية سامسونج "Samsung "، حيث بلغ حجم العينة التي أجريت عليها الدراسة 527 مفردة. و بغية الوصول إلى النتائج المستهدفة تم استخدام مجموعة من الأساليب الإحصائية أهمها: تحليل التباين الأحادي ANOVA One-Way، الوسط الحسابي، الانحراف المعياري و إختبار ت الأحادي One Sample T Test. و توصلت الدراسة إلى مجموعة من النتائج: *هنالك ولاء ذو دلالة إحصائية عند مستوى معنوية 0.05 للعلامة التجارية سامسونج "Samsung "؛ من طرف المستهلك الجزائري بإستخدام التسويق الفيروسي؛ *وجود فروق ذات دلالة إحصائية عند مستوى معنوية 0.05 لدرجة ولاء المستهلكين الجزائريين للعلامة التجارية سامسونج "Samsung "؛ بإستخدام التسويق الفيروسي؛ *هنالك أثر ذو دلالة إحصائية عند مستوى معنوية 0.05 للتسويق الفيروسي على ولاء المستهلكين الجزائريين للعلامة التجارية سامسونج "Samsung ". JEL : M31, L15 تصنيف Abstract: This research aims to study the loyalty of the Algerian consumer to the brand "Samsung" using viral marketing. To achieve the goal of the study, the researcher collected the necessary information by means of a questionnaire that was developed for this purpose after being tested for validity. The study was conducted on a soft sample that was chosen from the study community, and they are the Algerian consumer from the users of the brand "Samsung", A questionnaire was distributed on a convenient sample of (527) customers to distribute a questionnaire The following statistical techniques were employed: Frequencies, Means, Standard Deviation, ANOVA One – Way, Multiple Regression, and Alpha-Cronpach test. The researchers attained the following results: * There is statistically significant loyalty at the level of significance 0.05 for the brand "Samsung" by the Algerian consumer using viral marketing; * There are statistically significant differences at the level of significance of 0.05 to the degree of loyalty of the Algerian consumers to the brand "Samsung", using viral marketing; * There is a statistically significant effect of the 0.05 level of viral marketing on the loyalty of Algerian consumers to the brand "Samsung". JEL Classification Codes: M31, L15
Keywords: التسويق الفيروسي، الولاء للعلامة التجارية، القرار الشرائي، المستهلك الجزائري. ; viral marketing; loyalty brand; Purchasing decision; Algerian consumer